Solve for r

r=\frac{2\left(-3s+t-2\right)}{3}

$r=32(−3s+t−2) $

Solve for s

s=\frac{t}{3}-\frac{r}{2}-\frac{2}{3}

$s=3t −2r −32 $

Solve for t

t=\frac{3r}{2}+3s+2

$t=23r +3s+2$

Copy

Copied to clipboard

3r+6s=2t-4

Use the distributive property to multiply 3 by r+2s.

3r=2t-4-6s

Subtract 6s from both sides.

3r=-6s+2t-4

The equation is in standard form.

\frac{3r}{3}=\frac{-6s+2t-4}{3}

Divide both sides by 3.

r=\frac{-6s+2t-4}{3}

Dividing by 3 undoes the multiplication by 3.

r=\frac{2t}{3}-2s-\frac{4}{3}

Divide -4+2t-6s by 3.

3r+6s=2t-4

Use the distributive property to multiply 3 by r+2s.

6s=2t-4-3r

Subtract 3r from both sides.

6s=-3r+2t-4

The equation is in standard form.

\frac{6s}{6}=\frac{-3r+2t-4}{6}

Divide both sides by 6.

s=\frac{-3r+2t-4}{6}

Dividing by 6 undoes the multiplication by 6.

s=\frac{t}{3}-\frac{r}{2}-\frac{2}{3}

Divide 2t-4-3r by 6.

3r+6s=2t-4

Use the distributive property to multiply 3 by r+2s.

2t-4=3r+6s

Swap sides so that all variable terms are on the left hand side.

2t=3r+6s+4

Add 4 to both sides.

\frac{2t}{2}=\frac{3r+6s+4}{2}

Divide both sides by 2.

t=\frac{3r+6s+4}{2}

Dividing by 2 undoes the multiplication by 2.

t=\frac{3r}{2}+3s+2

Divide 3r+6s+4 by 2.